THE INSTRUCTIONAL PRACTICES OF SECONDARY SCHOOL TEACHERS IN ETHIOPIA: HULET EJU ENESIE WOREDA - ZEKIROS, BIZU KINFE (International Journal of Research -GRANTHAALAYAH, 2020)
This study was examined secondary school teachers’ instructional practices by using First Principle of Instruction model as guiding principle. Both qualitative and quantitative methods were employed. The total populations of the study were 52. From these 40 Biology teachers, 4 directors, 4 supervisors and 4 department heads were selected through comprehensive sampling technique. Data were obtained through questionnaire, interview, classroom observation and document analysis. Various statistical tools such as mean, frequency and percentage were applied to analyze the data. The finding indicated that secondary school Biology teachers design their lessons by using First Principle of Instruction Model and they practiced it partially. And biology teacher’s instructional practices are aligned partially with First Principle of Instructional Model. Some factors that affect the design and implementation of the lessons based on the First Principle of Instruction model were identified: teachers’ related problems, students related problems, time constraints, policy issues, and resources. Based on the finding, it is recommended that woreda education office and general secondary schools should have to prepare short- and long-term training, seminars and workshop for teachers. Secondary school directors and supervisors should help teachers to have personal, professional knowledge and pedagogical skill. They should also support them by creating good educational environment.